1979
DOI: 10.1111/j.1399-3054.1979.tb06304.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiology of Salt Excretion in Aeluropus litoralis (Graminae)

Abstract: Various aspects of salt excretion from leaves o( Aeluropus were investigated. Salt excretion exhibited an optimum-type of curve when measured against external salt concentration, while sodium content of the leaves increased linearly. The 'relative excretion', i.e. rate of excreted ions : change in leaf ion content, was maximal in the low salt concentration range, and decreased when external sodium chloride concentration increased. Concentration of the excreted droplets was higher than the external coneentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 17 publications
2
28
0
Order By: Relevance
“…Moreover, most investigations have dealt with salt impact on plant growth, nutrient relations (e.g. ion content, salt excretion) as well as water content (Pollak and Waisel 1979;Gulzar et al 2003). It is astonishing that no study to date has examined how salinity affects photosynthesis and, in this context, leaf anatomy and organelle ultrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most investigations have dealt with salt impact on plant growth, nutrient relations (e.g. ion content, salt excretion) as well as water content (Pollak and Waisel 1979;Gulzar et al 2003). It is astonishing that no study to date has examined how salinity affects photosynthesis and, in this context, leaf anatomy and organelle ultrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…The capacity of excretion to remove Na and Cl from the Warwick & Halloran (1991) reported variation for plant varies from species to species (Pollack & salinity tolerance among a number of Australian and Waisel, 1979;Waisel, Eshel & Agami, 1986; overseas accessions oi Diplachne fusca (L). Beauv.…”
Section: Introductionmentioning
confidence: 99%
“…Under natural conditions in the field, salt secretion tends to be heavily dependent on soil salinity (Rozema & Riphagen, 1977). Pollak & Waisel (1979) concluded that the optimal conditions for the efficiency of the excretion systems are a combination of low external salt concentration and high atmospheric humidity. It was found that increasing the external concentration of NaCl resulted in an increase in the amount of fluid secreted by salt glands of Limonium delicatulum to a high value at a level of k12 bar.…”
Section: mentioning
confidence: 99%
“…To test the efficiency of the excretion process, the relative excretion (which represents the ratio between absolute excretion and the change in internal Na + content) was computed according to Pollak & Waisel (1979). In this respect, Na + contents of the shoots (after washing), of the same individuals in which the transpiration and excretion rates were measured, were determined at the start and at the end of the experiment.…”
Section: Estimation Of Absolute and Relative Excretionmentioning
confidence: 99%
See 1 more Smart Citation